ARANTIKA RARANGGANIS DANCE - mira Agianti; Tati Narawati; Tatang Taryana (Journal of Dance and Dance Education Studies, 2022)
Narantika Rarangganis dance is a dance with a heroic theme and has its own characteristics, namely Narantika is performed by men, while Rarangganis is performed by women, has different movements but is performed in one song in the dance. The purpose of writing this article is to describe the background, choreographic structure, makeup and clothing of the Narantika Rarangganis Dance. This research uses a descriptive method.The participants in this research areheir,trainer and creator of Narantika Rarangganis Dance and Chairman of the Sunda Galih Pakuan Classical Dance Association, Bandung City. The technique used in data collection is the technique of observation, interviews, documentation. The results of this study are that there are Narantika dance movements which are the development of the Monggawa Dance in the Keurseus Dance family created by Raden Nugraha Soediredja as well as Rarangganis the development of the Kandagan Dance, which at that time Raden Nugraha Soediredja was assisted by Irawati Durban Ardjo and Indrawati Lukman.